2016
DOI: 10.1007/s10068-016-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analysis of walnut lipid extracts and properties as an anti-cancer stem cell regulator via suppression of the self-renewal capacity

Abstract: Colon cancer is a leading cause of cancer-related deaths worldwide. Effects of walnut ( L.) lipid extracts (WLEs) on the self-renewal capacity of cancer stem cells (CSCs) in colon cancer were investigated. The dominant component of WLEs was α-linoleic acid (64.6%), followed by α-linolenic acid (14.6%), and oleic acid (12.6%). A higher concentration of γ-tocopherol (37.1%) was also present than of α-tocopherol (0.6%). CD133CD44CSCs treated with WLEs showed inhibition of colony formation and sphere formation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…(57) Walnut (Juglans regia L.) contains a complex array of natural compounds and phytochemicals, for instance, in the metaboliteprofiling analysis, walnut caused a significant increase in several polyunsaturated fatty acids (PUFAs), including DHA and 9-oxo-10(E),12(E)-octadecadienoic acid (9-oxoODA), as well as kynurenic acid, that exhibits a wide range of health benefits, including anti-inflammatory, antioxidative, and regenerating actions, by which dietary walnut supplementation (14% walnut) showed significant effects in recovery from dextran sulfate sodiuminduced colitis, (58) significant protection against fenitrothion-or malathion-mediated immunotoxicity, (59,60) enriching intestinal microbiome for improving health condition, (61) reducing telomere length, (62) ameliorating colitis and colitis-associated cancer, (63) suppressing colon cancer cell growth, (64) and regulating anticancer stem cells. (65) Though not touched in the current investiga-tion, cancer stem cell markers including CD133, CD44, DLK1, and Notch1 as well as the b-catenin/p-GSK3b signaling pathway were significantly down-regulated and the self-renewal capacity of CSCs was suppressed. Taken together with our investigation, WPE can impose significant cancer preventive action as well as anti-cancer effects in H. pylori infection.…”
Section: Discussionmentioning
confidence: 74%
“…(57) Walnut (Juglans regia L.) contains a complex array of natural compounds and phytochemicals, for instance, in the metaboliteprofiling analysis, walnut caused a significant increase in several polyunsaturated fatty acids (PUFAs), including DHA and 9-oxo-10(E),12(E)-octadecadienoic acid (9-oxoODA), as well as kynurenic acid, that exhibits a wide range of health benefits, including anti-inflammatory, antioxidative, and regenerating actions, by which dietary walnut supplementation (14% walnut) showed significant effects in recovery from dextran sulfate sodiuminduced colitis, (58) significant protection against fenitrothion-or malathion-mediated immunotoxicity, (59,60) enriching intestinal microbiome for improving health condition, (61) reducing telomere length, (62) ameliorating colitis and colitis-associated cancer, (63) suppressing colon cancer cell growth, (64) and regulating anticancer stem cells. (65) Though not touched in the current investiga-tion, cancer stem cell markers including CD133, CD44, DLK1, and Notch1 as well as the b-catenin/p-GSK3b signaling pathway were significantly down-regulated and the self-renewal capacity of CSCs was suppressed. Taken together with our investigation, WPE can impose significant cancer preventive action as well as anti-cancer effects in H. pylori infection.…”
Section: Discussionmentioning
confidence: 74%
“…(+)-Cathechin, chlorogenic acid and EA were identified as the main components of the extract, but their individual activity was not as effective as the entire mixture [ 123 ]. A lipid extract obtained from the fruit exhibited exactly the same activity on CCSCs: inhibition of CCSCs cloning and down-regulation of Notch1 and β-catenin expression and GSK3β phosphorylation [ 124 ]. ALA, LNA, a mix of PUFAs, and γ -tocopherol were the major components of this extract [ 124 ].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…A lipid extract obtained from the fruit exhibited exactly the same activity on CCSCs: inhibition of CCSCs cloning and down-regulation of Notch1 and β-catenin expression and GSK3β phosphorylation [ 124 ]. ALA, LNA, a mix of PUFAs, and γ -tocopherol were the major components of this extract [ 124 ]. It would be interesting to compare the composition of the mixtures in order to target the common compounds that promoted the biological effect, or alternatively, to investigate their additive or synergistic effect.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Walnuts (Juglans regia L.) are widely cultivated worldwide. [8][9][10] Studies have reported that walnuts contain 14-18% protein. [11,12] Its fat content is as high as 70%.…”
Section: Introductionmentioning
confidence: 99%